Nuclear coactivator protein p100 is present in endoplasmic reticulum and lipid droplets of milk secreting cells - Keenan, Thomas W.; Winter, Stefanie; Rackwitz, Hans-Richard; Heid, Hans W. (Biochimica et biophysica acta, 2000)
We have identified the p100 protein, previously known as a novel cellular coactivator, as a constituent of endoplasmic reticulum and cytosolic lipid droplets from milk secreting cells. Cytosolic lipid droplets of terminally differentiated mammary epithelial cells are secreted as milk lipid globules. However, milk lipid globules did not have detectable amounts of p100 protein. The p100 protein was found also in cytosol from lactating mammary gland, in storage lipid droplets from mouse adipocytes, and in endoplasmic reticulum from liver. Immunofluorescence microscopy of mammary epithelial cells confirmed the presence of p100 in non-nuclear regions of these cells. Partial sequence analysis of tryptic peptides from p100 from cow mammary gland showed extensive homology with the reported sequence of p100 determined from a human cDNA. Antibodies against a peptide synthesized to duplicate a sequence in human p100 recognized a protein of the size of p100 in cow, mouse and rat cell fractions.